2004
DOI: 10.1007/s00432-004-0555-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of S100 gene family in human esophageal squamous cell carcinoma

Abstract: The S100 gene family is closely associated with ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 30 publications
10
69
0
Order By: Relevance
“…A better understanding of the mechanisms regulating differentiation would offer the basis for identification of tumor biomarkers. Our previous study showed that S100A14 belongs to a subset of genes that are downregulated in esophageal cancers, and as one of many differentiation-associated genes, reduced S100A14 expression might contribute to esophageal carcinogenesis (17,18). Furthermore, our study showed that S100A14 regulated cell proliferation and apoptosis in a dose-dependent manner via interaction with RAGE in ESCC (15).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…A better understanding of the mechanisms regulating differentiation would offer the basis for identification of tumor biomarkers. Our previous study showed that S100A14 belongs to a subset of genes that are downregulated in esophageal cancers, and as one of many differentiation-associated genes, reduced S100A14 expression might contribute to esophageal carcinogenesis (17,18). Furthermore, our study showed that S100A14 regulated cell proliferation and apoptosis in a dose-dependent manner via interaction with RAGE in ESCC (15).…”
Section: Discussionmentioning
confidence: 50%
“…Confirmation of the reduced expression of S100A14 in ESCC compared with the matched normal epithelia by qRT-PCR Our previous study showed that S100A14 expression is downregulated in ESCCs versus adjacent normal tissue by semiquantitative RT-PCR (18). To further confirm the differential expression of S100A14 in ESCCs, we performed qRT-PCR analysis in 30 paired ESCCs and adjacent normal epithelial tissues.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We have classified overexpression as expression in a tumor tissue being 1.33-fold higher than that in the normal tissue. (18) Overexpression of S100A10 and B-FABP was confirmed (P < 0.05 and P < 0.005, respectively, χ 2 -test), but annexin II was not defined as overexpressed under this criterion. Then the 47 RCC cases were classified according to the nuclear grade and stage, and overexpression of three genes in each class was summarized (Table 1).…”
Section: Relationship Between Gene Expression and Prognostic Factors mentioning
confidence: 94%
“…More recently, however, S100A2-overexpressing cancers showed a trend toward preferentially developing lymph node metastases and distant metastases, suggesting that S100A2 might be related to the progression of esophageal SCC (Kyriazanos et al, 2002;Ji et al, 2004;Imazawa et al, 2005;Cao et al, 2009). …”
Section: Esophageal Squamous Cell Carcinoma (Escc)mentioning
confidence: 99%